2015
DOI: 10.1590/s1516-891320150232
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Potential Role of Silymarin Alone or in Combination with Vitamin E and/ or Curcumin on the Carbon Tetrachloride Induced Liver Injury in Rat

Abstract: The aim of this study was to investigate the effective role of silymarin either alone or in a combination with vitamin E and/or curcumin against the toxic impact of carbon tetrachloride (CCl4) induced liver injury The results revealed that administration of silymarin alone or in a combination with vitamin E and/or curcumin for 21 consecutive days, 24 h after CCl4 injection to rats, markedly ameliorated DNA damaged and apoptosis markers in rat livers, proinflammatory markers including tumor necrosis factor-α (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…On the contrary, it improved the antioxidant capacity and decreased the oxidative stress markers. These results are in accordance with the previous reports suggested that SIL possess antioxidant, antiapoptotic, anti-inflammatory and immunomodulatory properties (Al-Rasheed et al, 2015Fraschini et al, 2002;Karimi et al, 2011;Pradeep et al, 2007). The hepatoprotective role of SIL was suggested to be due to its enhancement of CYP2E1 activity which has a major role in drug metabolism (Dejanovic et al, 2014;Jorgačević et al, 2014;Mahli et al, 2015;Wong et al, 1998).…”
Section: Discussionsupporting
confidence: 91%
“…On the contrary, it improved the antioxidant capacity and decreased the oxidative stress markers. These results are in accordance with the previous reports suggested that SIL possess antioxidant, antiapoptotic, anti-inflammatory and immunomodulatory properties (Al-Rasheed et al, 2015Fraschini et al, 2002;Karimi et al, 2011;Pradeep et al, 2007). The hepatoprotective role of SIL was suggested to be due to its enhancement of CYP2E1 activity which has a major role in drug metabolism (Dejanovic et al, 2014;Jorgačević et al, 2014;Mahli et al, 2015;Wong et al, 1998).…”
Section: Discussionsupporting
confidence: 91%
“…The elevated serum ALT activity is consistent with the findings of several previous studies. [ 10 33 34 ] A number of histopathological alterations including necrosis, degenerated hepatocytes, inflammatory cells infiltration, dilated hepatic sinusoids, steatosis, and large patches of fibrous tissue are evident in CCl 4 -intoxicated rats. The present findings demonstrate that treatment of the intoxicated rats with SIL, alone and combined with CA and/or ME, potentially attenuated CCl 4 -induced hepatocellular injury.…”
Section: Discussionmentioning
confidence: 99%
“…The present findings demonstrate that treatment of the intoxicated rats with SIL, alone and combined with CA and/or ME, potentially attenuated CCl 4 -induced hepatocellular injury. Several studies have clearly reported that SIL,[ 10 34 ] CA[ 27 ] and ME[ 35 ] alleviated serum transaminases and histopathological alterations in rats. Interestingly, combination of SIL with CA or ME significantly ameliorated serum ALT and liver histological findings when compared with SIL alone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations